Efektifitas Pendamping Minum Tablet Tambah Darah terhadap Kadar Hemoglobin Ibu Hamil di Puskesmas Rappokalling Makassar - Nurana, Sitti; Hamang, Sitti Hadriyanti; Saputri, Linda Hardianti (An Idea Health Journal, 2024)
Indonesia has one of the highest Maternal Mortality Ratios (MMR) in Asia and ranks third highest among nations in the ASEAN area. The Maternal Mortality Ratio (MMR) in Indonesia, as indicated by the 2015 SUPAS statistics, was 305 deaths per 100,000 live births. The objective of this study is to assess the efficacy of companions supplement pills in increasing the hemoglobin levels of pregnant women. The study was carried out at the Rappokalling Makassar Community Health Center, employing a non-probability sampling method known as incidental sampling. The results of companions taking blood supplement tablets are effective on the hemoglobin levels of pregnant women with p value = 0.005, therefore, to increase the hemoglobin levels of pregnant women when health workers give blood supplement tablets, it is best to involve husband/family companions as supervisors of taking medication who have previously been educated by health workers.